Software Architecture Hour. (O'Reilly Media, Inc., 2023)
Join us for a special conversation with Neal Ford and Anna Shipman, technical director at the Financial Times (FT). They'll discuss how the company brought seven disparate technical groups into a single cohesive engineering group with one tech strategy, focusing on how the FT changes its strategy to meet changing business needs. They'll also delve into ways of aligning engineering work with business strategy, how to refresh the vision and communicate the strategy, and how to execute it and keep it on track. This is a chance for you to hear from Neal and Anna about software, architecture, and their own career journeys. They'll spend a few minutes covering the trends that are influencing architecture, then tell you what you need to know to stay ahead of the curve. What you'll learn and how you can apply it Learn how to craft technical strategy and make sure it's aligned to business needs See what's coming next with software architecture This recording of a live event is for you because... You want the chance to hear from Neal Ford and Anna Shipman about the alignment between strategy and software architecture and what the future might look like. You're looking for ways to grow your own skills and to act as an innovator in your organization. Recommended follow-up: Read Building Microservices, second edition (book) Read Enabling Microservice Success (book) Listen to Building Microservices, second edition (audiobook) Listen to Microservices Patterns (audiobook) Watch Software Architecture Superstream: Microservices (video).